MANAJEMEN KENDALI BANJIR DI KOTA PEKANBARU - Alfred Putra Anugerah Zebua; Zaili Rusli SD Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Flooding is an event that occurs when excessive flow of water immerses the city mainland. To overcome flooding, it is necessary to have a good flood control management so that the flood does not have a more severe impact, especially in handling flood emergency conditions. The purpose of this study is to find out flood control management in Pekanbaru City in handling flood emergency conditions and to find out factors which inhibits flood control management in Pekanbaru City. The theory used in this study is actuating theory according to G.R Terry and the flood control method used in this study is the method of handling emergency conditions according to Roberts J Kodoatie which consists of three important indicators, namely: flood prevention preparation, flood inspection, flood control coordination. The selection of research informants used the snowball sampling technique. Data collection techniques in this study are by interview, observation and documentation. The results of this study indicate that flood control management in Pekanbaru City especially in terms of handling flood emergency conditions conducted by the Public Works and Spatial Planning Service has not gone well because it only implemented two important indicators in handling flood emergency conditions, namely: flood prevention preparation and countermeasures coordination floods, but flood inspection indicators are not well implemented. In this study, there were found to be several inhibiting factors for flood control management in Pekanbaru, namely internal factors: such as lack of human resources and inadequate facilities and infrastructure, while external factors were difficult to reach, extreme climate change and lack of public awareness. For this reason, additional human resources are needed along with the addition of a transportation fleet to facilitate work.Keywords: Actuating, Flood Control Management, Flood Emergency Management